2020
DOI: 10.3390/su12114586
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Thinking Multiyear Study

Abstract: In the field of environmental sustainability and landscape management, geospatial thinking is necessary. A good level of geospatial thinking is related to academic success in engineering degrees. It is relevant, therefore, to detect the possible deficiencies that university students may have in tasks related to geospatial thinking. This research presents the results of a 2014‒2019 multiyear study with agricultural engineering students, in which seven geospatial tasks were analyzed. The statistical analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similar studies have shown that geospatial thinking helps students understand geographical data and influences the acquisition of geospatial knowledge (Perugini and Bodzin, 2020). And beyond that, individuals with strong geospatial thinking tend to succeed in the study (Carbonell-Carrera et al, 2020). In general, students' geospatial thinking can affect their academic achievement in geography (Aliman et al, 2019).…”
Section: Geospatial Thinkingmentioning
confidence: 82%
“…Similar studies have shown that geospatial thinking helps students understand geographical data and influences the acquisition of geospatial knowledge (Perugini and Bodzin, 2020). And beyond that, individuals with strong geospatial thinking tend to succeed in the study (Carbonell-Carrera et al, 2020). In general, students' geospatial thinking can affect their academic achievement in geography (Aliman et al, 2019).…”
Section: Geospatial Thinkingmentioning
confidence: 82%
“…Firstly, the three-dimensional modeling of the blocks and molds was performed using computational resources from the SketchUp PRO 2017 software, version 17.0.18899 64-bit for the construction of the desired geometries and 3D visualization [36,37].…”
Section: Three-dimensional Modeling Of Molds For Manufacture Of Polym...mentioning
confidence: 99%
“…Therefore, in comparison with conventional education, STEM education improves by considering and reinforcing SI (28). This turns SI into a major component in STEM education, and many studies emphasized the importance of this integration (29,30,31).…”
Section: Introductionmentioning
confidence: 99%